Influence of angulation and vertical misfit in the evaluation of micro-deformations around implants - Rodrigues, Vinícius Anéas; Tribst, João Paulo Mendes; Santis, Leandro Ruivo de; Lima, Dimas Renó de; Nishioka, Renato Sussumu (Brazilian Dental Science, 2017)
Objective: This in vitro study was to evaluate micro-strains around of implant, under the influence of angulations and vertical misfit in three-element implant-supported fixed partial dentures during axial loading by using strain gauge analysis. Materials and Methods: Three external hexagon implants with straight configuration and three external hexagon implants with angled (17°) configuration were inserted into two polyurethane blocks. To measure micro-strain, four strain gauges were bonded onto the surface of each block. Plastic copings were adapted to a standard wax pattern and cast. An axial load of 30 kgf was applied on the center of each implant for 10 seconds, using a load application device. The vertical misfit was measured at six different points by using a stereo microscope with 100-X magnification. Results: The results showed that the values for different implant angulations were significant (P= 0.0086). The Pearson’s correlation test between micro-strain and vertical misfit revealed no correlation between angled configuration (P= 0.891) and straight configuration (P= 0.568). Conclusion: The micro strain was higher for angled implants; no correlation was found between the vertical misfit and the micro strain values.